Collect and culture of bull somatic cell Bos javanicus (Wagrer, 1844) for gene conservation - Son, Hoang Nghia; Ty, Le Van (Academia Journal of Biology, 2014)
Vietnam is a tropical country which has plentiful animals and plants, especially wide animals. Many animal species were listed in the Red Data Book of Vietnam (2000). However, many animal species were illegally hunted for aesthetic and economic purposes, for example bull. According to some points of view, bull somatic cells had the ability to develop in the DMEM added serum; besides, in our lab conditions, we have collected and cultured bull somatic cells to gene conservation for the making of materials for cloning later. Study results showed that bull somatic cells grew well in the DMEM medium added 10% FBS and we have collected a large number of typical firoblasts.